ENGLISH LANGUAGE COMPETENCY AND OUTSOURCED CALL CENTERS IN BANGLADESH - Rahman, Mizanur; Darus, Saadiyah; Hussain, Nazia (Jurnal Pendidikan Bahasa dan Sastra, 2015)
AbstractThis paper attempts to investigate whether or not the English competency of Customer Service Representatives (CSRs) is hindering the growth and development of outsourced call centers in Bangladesh. It also looks into the problems being faced by call centers in hiring English competent CSRs.  A limited appraisal of the English communication training of the CSRs offered by Call Centre Training Institutes is also within the purview of the paper. With this purpose 33 supervisors of different call centers, who are in charge of monitoring the CSRs, have been interviewed with a questionnaire comprised of both close and open ended questions.  The result shows there is scarcity of skilled English communicators which is one of the major barriers in the growth and development of the call centers. However, factors like product knowledge, intercultural communication skills, service personality are also crucial as they are integral for successful transaction and addressing them will pave the way for the progress of the industry. The result also implicitly indicates that mainstream education system in Bangladesh is still unable to produce competent English communicators.   The findings of the study reveal that the current shortage of skilled manpower can further become more acute when call center industry grows in line with the expectation of the government. It is also revealed that the call center training institutes are incapable of delivering the kind of training required for the aspirant CSRs. This study pinpoints the necessity of future research in several directions to ensure a balance between the demand and supply of native like fluent English communicators for call center Industry in Bangladesh. Keywords: English language competency, outsourced call centers, CRRs Abstrak Tulisan ini mencoba untuk menyelidiki apakah kompetensi bahasa Inggris Perwakilan Layanan Pelanggan (Customer Service Representatives/CSR) menghambat pertumbuhan dan perkembangan pusat-pusat panggilan pengalihluaran di Bangladesh. Tulisan ini juga menyelidiki masalah yang dihadapi oleh pusat panggilan dalam mempekerjakan CSR yang berkompeten dalam bahasa Inggris. Sebuah penilaian terbatas dari pelatihan komunikasi bahasa Inggris bagi CSR yang ditawarkan oleh Lembaga Pelatihan Pusat Panggilan akan menjadi pembahasan dalam artikel ini. Untuk mencapai tujuan ini, 33 pengawas dari pusat-pusat panggilan yang berbeda, yang bertugas memantau CSR, telah diwawancarai dengan kuesioner terdiri dari pertanyaan tertutup dan terbuka. Hasilnya menunjukkan ada kelangkaan staf yang terampil dalam bahasa Inggris yang menjadi salah satu hambatan utama dalam pertumbuhan dan perkembangan pusat panggilan. Namun, faktor-faktor seperti pengetahuan produk, kemampuan komunikasi antarbudaya, kepribadian layanan juga berperan penting karena semuanya merupakan bagian integral transaksi yang berhasil dan upaya peningkatan semua faktor tersebut akan membuka jalan bagi kemajuan industri. Hasilnya juga secara implisit menunjukkan bahwa sistem pendidikan utama di Bangladesh masih mampu menghasilkan individu yang berkompeten dalam bahasa Inggris. Temuan penelitian ini juga mengungkapkan bahwa kekurangan tenaga kerja yang terampil dapat menjadi lebih parah ketika industri pusat panggilan tumbuh sejalan dengan harapan pemerintah. Terungkap juga bahwa lembaga pelatihan pusat panggilan tidak mampu menyediakan jenis pelatihan yang dibutuhkan oleh para calon CSR. Penelitian ini menunjukkan perlunya penelitian masa depan di beberapa aspek untuk memastikan keseimbangan antara permintaan dan pasokan individu yang fasih berbahasa Inggris seperti penutur jati untuk Industri pusat panggilan di Bangladesh. Kata kunci: Kompetensi bahasa Inggris, pusat panggilan pengalihluaran, CSR